Prospects for electron beam aberration correction using sculpted phase masks - Shiloh, Roy; Remez, Roei; Arie, Ady (Ultramicroscopy, 2016)
Technological advances in fabrication methods allowed the microscopy community to take incremental steps towards perfecting the electron microscope, and magnetic lens design in particular. Still, state of the art aberration-corrected microscopes are yet 20-30 times shy of the theoretical electron diffraction limit. Moreover, these microscopes consume significant physical space and are very expensive. Here, we show how a thin, sculpted membrane is used as a phase-mask to induce specific aberrations into an electron beam probe in a standard high resolution TEM. In particular, we experimentally demonstrate beam splitting, two-fold astigmatism, three-fold astigmatism, and spherical aberration.
Created from Fastlane, Scopus look-up
Keywords: Aberration correction; Electron column; Phase-masks; Phase-plates; Thin film membranes